Bleeding Time and Platelet Volume in Acute Myocardial Infarction – A 2 Year Follow-Up Study - Kristensen, S Dalby; Milner, P C; Martin, J F (Thrombosis and Haemostasis, 1988)
The bleeding time is shortened and the mean platelet volume is increased in the acute phase of myocardial infarction. In this follow-up study we repeated the measurement of the bleeding time, the platelet count and the platelet volume distribution in 18 patients who had suffered from a definite acute myocardial infarction two years before and in 16 control patients who had been admitted with chest pain but no definite myocardial infarction at that time. At the time of follow-up the bleeding time was significantly lengthened in the myocardial infarction group (median values = 169 s and 209 s respectively), whereas it had shortened in the control group (median values = 258 s and 228 s respectively). Comparison of the platelet volume distribution curves of the myocardial infarction patients at time of infarction and 2 years later revealed a significantly higher percentage of small platelets and significantly lower percentages of both medium-sized and large platelets at the time of infarction. These changes in the platelet volume distribution could indicate consumption of medium-sized and large platelets at the time of myocardial infarction. None of the measured variables predicted which of the patients with acute myocardial infarction would subsequently re-infarct or die. In the patients studied with definite ischaemic heart disease (n = 26) a significant negative correlation between bleeding time and mean platelet volume was found. The shortened bleeding time in myocardial infarction is related to the acute event itself or preceeds it, but is reversed two years later.
Keywords: Acute myocardial infarction; Bleeding time; Platelets; Platelet volume